Vpliv književnosti Franza Kafke na nekatere vidike kritične kulturne teorije - Mlačnik, Primož (Slavia Centralis, 2021)
In this article, we provide an overview of critical interpretations of Franz Kafka’s literature by authors from the field of critical cultural studies. We show that many intellectuals in this field have created theories under the (in)direct influence of Kafka’s literature and thus have consolidated Kafka as a canonical writer. We outline similarities and common problems in the field of cultural studies and Kafka studies including the relationship toward modernity, a critique of the idea of progress, the question of cultural minorities and identities, and the problem of signification. In this discussion, we attempt to show the reciprocal link between modernist literature and postmodernist cultural theory.
Keywords: Franz Kafka; critical interpretations; cultural studies; modernist literature; commonalities and problems